LEADERSHIP STYLES AND WORK ENGAGEMENT: AN INVESTIGATION INTO EFFECTIVE LEADERSHIP PRACTICE - Mendrofa, Syah Abadi (Management Studies and Business Journal (PRODUCTIVITY), 2024)
Significant changes in the world of work, particularly due to the COVID-19 pandemic, have prompted many organizations to adapt to hybrid and remote work models. Even though digital leadership is a crucial factor in increasing work engagement, not much research has explored the influence of digital leadership style on employee engagement in this context. This research aims to analyze various digital leadership styles and their impact on work engagement in hybrid and remote work environments through a systematic literature review approach. The research results show that leadership styles such as transformational, servant, and agile leadership have a positive impact on employee engagement, while transactional leadership styles tend to be less effective in this context. The implications of this research provide insights for leaders to adopt a more adaptive and humane approach in increasing employee engagement in a dynamic digital work environment.